Imperial Subjugations: Colonialism and Race After Marx - Mandin, Gareth (Université d'Ottawa / University of Ottawa, 2018)
Drawing on Foucault’s conception of “subjugated knowledges,” this thesis attempts to articulate a subjugated anti-colonial reading of Marx so as to interrogate the discursive modifications effected within Marxism after Marx, specifically as those modifications relate to the conditions of possibility regulating Marxist understandings of race and colonialism. This genealogy proceeds by offering a critical re-examination of the ways in which Marxists of the Second International theorized a “modern,” “scientific” account of imperialism, one that expunged important insights into the nature of colonial-capitalism at the same time it established a new knowledge of capitalist expansion and the world market. This Leninist schematization of imperialism is theorized in relation to “deraceination,” a neologism arising from this project and describing the manifold discursive processes by which Marxism was uprooted from its grounding materialist premises while it underwent an ideological de-racialization that eschewed discussions of race and Indigeneity in Marxist political economy. After this critique of the Leninist schematization of imperialism, deraceination is elaborated by revisiting the early history of Marxist feminism, leading to the conclusion that the historical subjugation of the basic materiality of race and gender was accomplished in no small part through the definition of “the woman question.” By liberating this subjugated trajectory of Marxist thought, this thesis argues for the necessity of reincorporating an anti-colonial reading of Marx into our understandings of Marxism and Marxist feminism.
Keywords: Marxism; Colonialism; Political Economy; Marxist Feminism; Karl Marx; Imperialism